Krisis Ekonomi dalam Perspektif Islam - Siti Kadariah; M. Shabri Abd. Majid (Jurnal EMT KITA, 2023)
This research discusses descriptively the causes of the economic crisis and the approaches and analyzes of many experts who provide solutions to the economic crisis that has occurred. The occurrence of an economic crisis in Islam cannot be separated from economic practices or activities that are carried out contrary to Islamic values, such as the act of consuming usury, monopoly, corruption, and other malpractice actions. Islamic Economics and the Economic Crisis are an approach and analysis. provide solutions to the current economic crisis. Although there are differences, in general the key to solving the crisis is to eliminate the system of interest (usury) in the economy. In terms of banking, Islamic economics has provided solutions (alternatives) to avoid the practice of usury (interest) in the banking process. The solution is in the form of a Mudharabah product based on a profit sharing ratio expressed in the form of a percentage between shahibul mal and mudharib.